Medical Computer Vision: Algorithms for Big Data International Workshop, MCV 2015, Held in Conjunction with MICCAI 2015, Munich, Germany, October 9, 2015, Revised Selected Papers - Menze, Bjoern; Langs, Georg; Montillo, Albert; Kelm, Michael; Müller, Henning; Zhang, Shaoting; Cai, Weidong; Metaxas, Dimitris (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2016)
This book constitutes the thoroughly refereed prost-workshop proceedings of the International Workshop on Medical Computer Vision: Algorithms for Big Data, MCS 2015, held in Munich, Germany, in October 2015, held in conjunction with the 18th International Conference on Medical Image Computing and Computer-Assisted Intervention, MICCAI 2015. The workshop shows well the current trends and tendencies in medical computer vision and how the techniques can be used in clinical work and on large data sets. It is organized in the following sections: predicting disease; atlas exploitation and avoidance; machine learning based analyses; advanced methods for image analysis; poster sessions. The 10 full, 5 short, 1 invited papers and one overview paper presented in this volume were carefully reviewed and selected from 22 submissions.